2011
DOI: 10.1007/s00128-011-0307-y
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated Compounds in Water, Sediment and Soil from Guanting Reservoir, China

Abstract: Concentrations of 12 perfluorinated compounds (PFCs) were measured in 21 representive water, sediment and soil samples from Guanting Reservoir and vicinity. Perfluorooctanoic acid (PFOA) was the predominant PFCs with concentrations of 0.55-2.3 ng/L, \LOQ to 0.68 ng/g dw and \LOQ to 2.8 ng/g dw in water, sediment and soil, respectively. Perfluorododecanoic acid (PFDoA) was frequently detected in solid matrices, with concentrations of \LOQ to 0.18 ng/g dw in sediment and 0.13-0.26 ng/g dw in soil. PFCs were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Concentrations of PFOA and PFOS were significantly less than the residential soil screening guidance values issued by US-EPA (PFOA, 16,000 ng/g; PFOS, 6,000 ng/g) (US-EPA 2009). Results obtained from the present study were compared with those previously reported in other areas (Table 3) (Wang et al 2011;Wang et al 2012a;Meng et al 2013a;Naile et al 2010;Li et al 2010). Basically, Concentrations of PFASs around the Koshi River were less than those reported from the areas with higher level of industrialization, such as Shanghai, Tianjin Binhai New Area in Chin and the west coast of South Korea.…”
Section: Resultssupporting
confidence: 45%
“…Concentrations of PFOA and PFOS were significantly less than the residential soil screening guidance values issued by US-EPA (PFOA, 16,000 ng/g; PFOS, 6,000 ng/g) (US-EPA 2009). Results obtained from the present study were compared with those previously reported in other areas (Table 3) (Wang et al 2011;Wang et al 2012a;Meng et al 2013a;Naile et al 2010;Li et al 2010). Basically, Concentrations of PFASs around the Koshi River were less than those reported from the areas with higher level of industrialization, such as Shanghai, Tianjin Binhai New Area in Chin and the west coast of South Korea.…”
Section: Resultssupporting
confidence: 45%
“…The LOQ of PFOS accounts to 0.00005 and 0.01 µg kg -1 for water and soil samples, respectively. The mass instrument and proficiency differences gave lower LOQs than previously reported values (Naile et al 2010;Wang et al 2011). The precisions of PFOA and PFOS were 4.3 and 5.8% for water, and 3.4 and 5.8% for soil, respectively.…”
Section: Quality Assurancementioning
confidence: 53%
“…Soil PFOA and PFOS in the soil samples were extracted using a method similar to that described by Wang et al (2011). Briefly, samples were dried in a drying oven at 80°C, homogenized and passed through a 2-mm sieve.…”
Section: Sample Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the sediment samples from the Xiaoqing River revealed a much higher level of PFOA which ranged from 3.86 to 456.20 ng/g dw and a mean concentration of 103.14 ng/g dw. It therefore, indicated that the study area was in the condition of more serious PFOA pollution compared to the counterparts of the South Bohai coastal rivers ranging from 0.01 to 1.05 ng/g dw, the North Bohai coastal rivers lower than 0.54 ng/g dw (Wang et al, 2011) and the Pearl River in China (0.09e0.28 ng/g dw) (Bao et al, 2010). The highest concentrations of P PFAA (465.60 ng/g dw) and PFOA (456.20 ng/g dw) were found at site XQ5, which was located downstream close to the effluent from one fluorochemical facility that produced PTFE and other fluoropolymers with massive capacity.…”
Section: Resultsmentioning
confidence: 87%